2004
DOI: 10.1037/0735-7028.35.2.185
|View full text |Cite
|
Sign up to set email alerts
|

Managed Care and the Independent Practice of Psychology.

Abstract: Heritage Professional AssociatesHow has managed care impacted the independent practice of psychology? The present article reports on data from 2 national surveys (from 1996 and 2001) that address this question. Both surveys indicated that managed care was a source of stress, with external constraints, paperwork, and managed care reimbursement being the most highly rated stresses. These stresses had not increased in the 5 years between surveys, and the most recent survey suggested that, overall, psychologists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 37 publications
4
37
0
Order By: Relevance
“…Third, there is great variability among clinical settings, and therefore, results obtained from benchmarking one type of clinical settings (e.g., managed care) may not be generalizable to other clinical settings (e.g., university and college counseling centers). Last but not least, the variability among therapists in based on differences in their work condition, including selection, training, workload and stress, and supervision need to be taken into account (e.g., Rounsaville et al, 1988;Rupert and Baird, 2004). Therefore, the possible qualitative differences between the effect sizes obtained from the clinical settings data and the clinical trials benchmarks negate a simple conclusion based solely on numerical differences in effect sizes; unless complete qualitative equivalence regarding the above factors could be established between the clinical settings and clinical trials, it would be a gross misuse of the benchmarking strategy if definitive conclusions were drawn regarding differences in effectiveness and efficacy by its use.…”
Section: Discussionmentioning
confidence: 99%
“…Third, there is great variability among clinical settings, and therefore, results obtained from benchmarking one type of clinical settings (e.g., managed care) may not be generalizable to other clinical settings (e.g., university and college counseling centers). Last but not least, the variability among therapists in based on differences in their work condition, including selection, training, workload and stress, and supervision need to be taken into account (e.g., Rounsaville et al, 1988;Rupert and Baird, 2004). Therefore, the possible qualitative differences between the effect sizes obtained from the clinical settings data and the clinical trials benchmarks negate a simple conclusion based solely on numerical differences in effect sizes; unless complete qualitative equivalence regarding the above factors could be established between the clinical settings and clinical trials, it would be a gross misuse of the benchmarking strategy if definitive conclusions were drawn regarding differences in effectiveness and efficacy by its use.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the selection and number of tests, and the time devoted to them, have decreased in frameworks of managed care [15]. …”
Section: Introductionmentioning
confidence: 99%
“…For example, a study of professional psychologists found that increased administrative and paperwork hours were associated with greater emotional exhaustion and burnout (Rupert & Morgan, 2005). Other studies have found that paperwork was among the greatest stressors (Rupert & Baird, 2004) and challenges (Kantorowski, 1992) reported among professionals in the mental health field.…”
Section: Introductionmentioning
confidence: 99%